(untitled) (Statistics, Optimization & Information Computing, 2025)
This paper presents a smart, knowledge-driven system designed to optimize Agile Project Management (APM) processes, particularly for Industry 4.0 applications. By formalizing key concepts and integrating Rule Based Reasoning using Semantic Web Rule Language (SWRL) inference rules, the proposed APM ontology offers a robust framework for projects 4.0 knowledge management, interoperability, and decision support. The proposed ontology-based system lies in its capacity to integrate data from external systems, enabling holistic optimization and supporting intelligent decision-making. The system enhances task prioritization, resource allocation, and sprint planning by leveraging reasoning capabilities to streamline project workflows and reduce redundancy. Its implementation in a real-world cobot integration project demonstrated its ability to align tasks with project objectives, optimize resource utilization, and ensure efficient project execution.